Comparative Genome Analysis of Vibrio vulnificus, a Marine Pathogen - Chen, Chung-Yung; Wu, Keh-Ming; Chang, Yo-Cheng; Chang, Chuan-Hsiung; Tsai, Hui-Chi; Liao, Tsai-Lien; Liu, Yen-Ming; Chen, Hsiang-Ju; Shen, Arthur Bo-Ting; Li, Jian-Chiuan; Su, Teh-Li; Shao, Chung-Ping; et al. (Genome Research, 2003)
The halophile Vibrio vulnificus is an etiologic agent of human mortality from seafood-borne infections. We applied whole-genome sequencing and comparative analysis to investigate the evolution of this pathogen. The genome of biotype 1 strain, V. vulnificus YJ016, was sequenced and includes two chromosomes of estimated 3377 kbp and 1857 kbp in size, and a plasmid of 48,508 bp. A super-integron (SI) was identified, and the SI region spans 139 kbp and contains 188 gene cassettes. In contrast to non-SI sequences, the captured gene cassettes are unique for any given Vibrio species and are highly variable among V. vulnificus strains. Multiple rearrangements were found when comparing the 5.3-Mbp V. vulnificus YJ016 genome and the 4.0-Mbp V. cholerae El Tor N16961 genome. The organization of gene clusters of capsular polysaccharide, iron metabolism, and RTX toxin showed distinct genetic features of V. vulnificus and V. cholerae. The content of the V. vulnificus genome contained gene duplications and evidence of horizontal transfer, allowing for genetic diversity and function in the marine environment. The genomic information obtained in this study can be applied to monitoring vibrio infections and identifying virulence genes in V. vulnificus.